Biological Control of Bacterial Grain Rot Disease Caused by Burkholderia glumae Using Actinomycetes - Nurmujahidin; Giyanto, Giyanto; Dadang (Jurnal Fitopatologi Indonesia, 2023)
Biological Control of Bacterial Grain Rot Disease Caused by Burkholderia glumae Using ActinomycetesBacterial grain rot disease is an important disease in rice plants caused by the bacterium Burkholderia glumae and causes yield loss up to 70%. In general, it is recommended to control this disease by seed treatment using various biological agents, including actinomycetes which produce antibacterial bioactive compounds. The aim of this study was to obtain actinomycetes strains that have the potential to control bacterial grain rot caused by B. glumae. The stages of the research included isolating and screening actinomycetes as potential biological agents against B. glumae, testing the phytotoxicity of actinomycetes on rice seeds, and testing the effectiveness of actinomycetes in controlling B. glumae on rice in the nursery phase. There were 40 actinomycetes isolated from rice plants and the rhizosphere and 17 of them had no potential as pathogens for plants or mammals. The suppression potency of the actinomycetes based on antibiosis test yielded 7 actinomycetes strains that were able to suppress the development of B. glumae and 5 strains had an inhibition zone of more than 2 mm, were not phytotoxic to rice plants and had the ability to promote plant growth. This actinomycete strain affects the growth of B. glumae and also suppresses the degree of its infection. Actinomycetes ST1, ST27, and BT23 strains were effective in suppressing bacterial grain rot in the nursery phase.